Mechanical model and numerical analysis of a method for local rock reinforcing to control the floor heave of miningaffected roadway in a coal mine - Sakhno, I. G.; Sakhno, S. V.; Kamenets, V. I.; Сахно, І. Г.; Сахно, С. В.; Каменець, В. І. (IOP Publishing, 2022)
A floor heave controlling method has been substantiated, based on the creation of locally reinforced zones of a special shape in roadway floor, which allows saving stability even with a low rocks friction ratio. The method is based on a mechanical model of the formation of an increasing strength spacer system in roadway floor. The numerical analysis of rock massif stress-strain state carried out by the finite element method, has made it possible to determine the mechanism of floor heave during rock reinforcing. The performed analysis of the simulation results has made it possible to determine the influence of the quality of rock reinforcing and the rock friction ratio value on the amount of heave in the mining-affected roadway. The effectiveness of the proposed method has been proven as a result of a comparative analysis.